Mundkur Memorial Lecture - Emerging problems in plant bacteriology - VERMA, J.P. (Indian Phytopathology, 2012)
The world has become divided into nations that know how to manage technologies to create wealth, and nations that do not know how to do this. Actually, mankind has always found it easier to destroy wealth than to create it, and no country has developed and become advanced (industrial country) since world war-I; whereas between 1860 and 1910 a new major industrial nation emerged every 20 years or so. It must be remembered that output of agriculture created wealth for the industrialisation of Europe and USA; Japan's development was financed by the export of silk.